Implementation of the Development Planning Deliberation Policy (Musrenbang) in Sumur Bandung Sub District - Arifin, Farid; Kurniadi, Budi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The implementation of the Development Planning Deliberation Policy in Kecamatan Sumur Bandung is still not optimal because in its implementation, of all the proposals made, more proposals are rejected than accommodated. So in line with this right, the purpose of this study is to find out what underlies that the community's proposals are not well accommodated. The theory of policy implementation from Merille S. Grindle which contains at two dimensions, namely policy content and implementation environment. The research method used is descriptive, data collection techniques through observation, in-depth interviews and documentation. The results of this study indicate that in the context of the Development Planning Deliberation with the analysis of Merille S. Grindle's theoretical approach which shows that there are still 3 aspects that have not been fulfilled aspects of Interest Affected, Resources Committed and Compliance and Responsiveness. This results in the low number of community proposals that are accommodated due to the incompatibility of community proposals with the established Development Planning Deliberation policies. If the Development Planning Deliberation in its implementation is analysed with a policy theory approach and the meaning obtained from field data.